2020
DOI: 10.1080/10643389.2020.1801308
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of microplastic pollution in urban freshwater environments and legislative progress in China: Recommendations and insights

Abstract: A critical review of microplastic pollution in urban freshwater environments and legislative progress in China: recommendations and insightsFreshwater systems are vitally important, supporting diversity and providing a range of ecosystem services. In China, rapid urbanization (over 800 million urban population) has led to multiple anthropogenic pressures that threaten urban freshwater environments.Microplastics (<5 mm) result from intensive production and use of plastic materials, but their effects in urban fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Strady et al assessed baselines of microplastic concentrations in selected marine and freshwater environments ( Strady et al, 2021 ). Xu et al reviewed microplastic pollution in urban freshwater watersheds in China and identified key knowledge and policy gaps that need to be filled to improve understanding of the environmental risks of microplastics ( Xu et al, 2021a ). Ding, et al reviewed the source, fate and toxicity of microplastics in freshwater ecosystems ( Ding et al, 2021 ).…”
Section: Results and Analysismentioning
confidence: 99%
“…Strady et al assessed baselines of microplastic concentrations in selected marine and freshwater environments ( Strady et al, 2021 ). Xu et al reviewed microplastic pollution in urban freshwater watersheds in China and identified key knowledge and policy gaps that need to be filled to improve understanding of the environmental risks of microplastics ( Xu et al, 2021a ). Ding, et al reviewed the source, fate and toxicity of microplastics in freshwater ecosystems ( Ding et al, 2021 ).…”
Section: Results and Analysismentioning
confidence: 99%
“…However, Tang et al (2018) and Chen H. et al (2020) reported a positive correlation between microplastic abundance and population number (not population density), and Tang et al (2018) reported a poor negative correlation between microplastic abundance and per capita GDP, which were contrary to the results of this study. These findings would play important roles in the first step of developing policy and regulations to mitigate the microplastic pollution risk (Xu et al, 2020).…”
Section: Microplastic Abundance Links To Socioeconomics In Chinamentioning
confidence: 92%
“…Research on microplastic pollution has been conducted simultaneously by a vast number of research teams [21][22][23]. It is also a popular subject of citizen science [24][25][26].…”
Section: Density Separation Methodsmentioning
confidence: 99%